2017
DOI: 10.1016/j.toxrep.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Health effects following subacute exposure to geogenic dust collected from active drainage surfaces (Nellis Dunes Recreation Area, Las Vegas, NV)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Such antigens require an appropriate response from both B cells, which secrete the antibody, and T cells, which ‘help’ the B cells. IgM levels were consistently and dose-responsively suppressed after exposure to each of the NDRA units in this study as well as previously published units [ [16] , [17] , [18] , [19] ]. These immune effects demonstrated from the complex mixture of metals are consistent with ‘arsenic only’ exposure studies that demonstrate a decrease in IgM humoral immune responses [ [37] , [38] , [42] , [43] , [44] ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such antigens require an appropriate response from both B cells, which secrete the antibody, and T cells, which ‘help’ the B cells. IgM levels were consistently and dose-responsively suppressed after exposure to each of the NDRA units in this study as well as previously published units [ [16] , [17] , [18] , [19] ]. These immune effects demonstrated from the complex mixture of metals are consistent with ‘arsenic only’ exposure studies that demonstrate a decrease in IgM humoral immune responses [ [37] , [38] , [42] , [43] , [44] ].…”
Section: Discussionsupporting
confidence: 91%
“…It might be considered that this excess iron from the exposure presented a possible compensatory factor to drive hemoglobin synthesis by increased ferritin cellular stores or increased saturation of transferrin. In the NDRA, CBN 5 and dust from drainage sediments that were analyzed in a previous study [ 19 ] were the only two sediment types that showed any effect on red blood cell physiology and it should be noted that they contained the highest levels of lead compared to all other NDRA geogenic dust samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, a reduced concentration of IgM antibodies against myelin basic protein (MBP) was found by DeWitt et al [122] in mice exposed to geogenic dust from arsenic-rich sediment (including vanadium) at NDRA. IgM antibodies against MBP were also reduced in mice exposed to geogenic dust (including vanadium) collected from active drainage surfaces (NDRA) [123]. Finally, studies of the levels of vanadium in some internal organs of rodents (in an inhalation model) conducted by Sánchez et al [114] revealed elevated concentrations of this metal in the brain of mice.…”
Section: Neurotoxic Effects Of Vanadium After Inhalation In Animals-a...mentioning
confidence: 99%
“…Summary of neurotoxic effects of vanadium after inhalation: studies in laboratory animals and those naturally exposed to urban air. Elaborated on the basis of the available literature data[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]. Ab: antibody, AG-rats: African giant rats, AP site: apurinic/apyrimidinic site, CNS: central nervous system, DA: dopamine, GFAP: glial fibrillary acidic protein; IgM; immunoglobulin M, iNOS: inducible nitric oxide synthase, MBP: myelin basic protein, MMPs: matrix metalloproteinases, NF-kB: nuclear factor kappa B, NF68: neurofilament 68 protein; TH: tyrosine hydroxylase, V: vanadium.…”
mentioning
confidence: 99%